Mode Shifting Probability of Working People to Angkot: Is there Any Hope for Angkot to Survive in Bandung City? - Lisna Rahayu (The Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Bandung is one of Indonesia’s major cities, holding a strategic position as the center of the Bandung Metropolitan Area. The most dominant paratransit with the widest coverage in Bandung City is the angkot, a small four-wheeled vehicle (minibus) that has been modified for use as public transportation. As it stands currently, however, this paratransit service is inadequate and unreliable, and it has pushed people to use private vehicles to support their daily commute, which causes traffic congestion to worsen. Workers are the biggest traffic-generating group in Bandung city. Their regular commute pattern as well as their large proportion in Bandung city’s population (47.78% of the total population in 2020) make this group an important determinant in Bandung City’s transportation. Shifting the workers’ mode of transportation from private to public transportation including the angkot is predicted to decrease traffic jams on some level. Through binary logistic regression, this study provides an analysis of mode shifting probability to the angkot, key factors that could be intervened to increase this shifting probability, as well as the extent to which intervention toward these factors will increase angkot usage so that it can provide a picture of future characteristics of the angkot in contrast to the current condition, should this transportation mode continue to run in the future. Based on the modeling result, the study identified four key variables that significantly influence mode shifting probability in Bandung City: 1) private vehicle ownership, 2) driving license ownership, 3) people’s perception of current transportation costs, and 4) people’s perception of the level of comfort provided by the mode of transportation. If in the future the angkot in Bandung City is improved with better comfort and affordability, approximately only 3.31% of workers will start using the angkot. This very low probability indicates that if in the future the government wants to shift working people from private vehicles to the angkot, then the angkot must be transformed. Abstrak. Bandung merupakan salah satu kota besar di Indonesia yang memiliki posisi strategis sebagai pusat kawasan metropolitan. Paratransit yang paling dominan dengan jangkauan terluas di Kota Bandung adalah angkot, kendaraan roda empat kecil (minibus) yang telah dimodifikasi untuk digunakan sebagai transportasi umum. Namun, layanan paratransit ini tidak memadai dan tidak dapat diandalkan sehingga mendorong orang untuk menggunakan kendaraan pribadi dalam mendukung perjalanan sehari-hari, yang menyebabkan kemacetan lalu lintas semakin parah. Pekerja merupakan kelompok penghasil lalu lintas terbesar di kota Bandung. Pola komuter yang teratur serta proporsi penduduk kota Bandung yang besar (47,78% dari total penduduk pada tahun 2020) menjadikan kelompok ini sebagai determinan penting dalam transportasi Kota Bandung. Pergeseran moda transportasi pekerja dari angkutan pribadi ke angkutan umum termasuk angkot diprediksi dapat mengurangi kemacetan di beberapa tingkatan. Melalui regresi logistik biner, penelitian ini memberikan analisis probabilitas perpindahan moda ke angkot, faktor-faktor kunci yang dapat diintervensi untuk meningkatkan probabilitas perpindahan tersebut, serta sejauh mana intervensi terhadap faktor-faktor tersebut akan meningkatkan penggunaan angkot sehingga dapat memberikan gambaran karakteristik angkot di masa depan yang kontras dengan kondisi saat ini, dalam kasus moda transportasi ini tetap berjalan di masa yang akan datang. Berdasarkan hasil pemodelan, penelitian ini mengidentifikasi empat variabel kunci yang berpengaruh signifikan terhadap probabilitas perpindahan moda di Kota Bandung: 1) kepemilikan kendaraan pribadi, 2) kepemilikan SIM, 3) persepsi masyarakat terhadap biaya transportasi saat ini, dan 4) persepsi masyarakat terhadap tingkat kenyamanan yang diberikan oleh moda transportasi tersebut. Jika kedepannya angkot di Kota Bandung ditingkatkan dengan kenyamanan dan keterjangkauan yang lebih baik, kira-kira hanya 3,31% pekerja yang akan mulai menggunakan angkot. Probabilitas yang sangat rendah ini menunjukkan bahwa jika di masa depan pemerintah ingin memindahkan pekerja dari kendaraan pribadi ke angkot, maka angkot tersebut harus diubah. Kata kunci. Pergeseran moda, angkot, pekerja, logistik biner.